The insulin-like growth factor system and colorectal cancer: clinical and experimental evidence - Davies, M; Gupta, S; Goldspink, G; Winslet, M (SPRINGER, 2006)
Objective: The aim of this review is to clarify the involvement of the insulinlike growth factor (IGF) system in the development of colorectal malignancy. Materials and methods: Medline searches were used to identify key articles relating the IGF system with the development of colorectal cancer. Results: The IGF system has been linked to colorectal malignancy by a convergence of data from epidemiological, clinical and laboratory-based sources. Conclusion: Further work is needed to characterise the IGF system expression in the colon. Such clarification could lead to the identification of targets that can be manipulated for clinical advantage.